2021
DOI: 10.12809/hkjr2117253
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Results of Palliative Stereotactic Radiotherapy of Barcelona Clinic Liver Cancer Stage C Hepatitis B–Related Hepatocellular Carcinoma

Abstract: Objective: To assess the long-term effectiveness of palliative stereotactic body radiotherapy (SBRT) in patients with large unresectable Barcelona Clinic Liver Cancer stage C hepatitis B-related hepatocellular carcinomas (HCCs). Methods: Consecutive HCC cases treated with fractionated SBRT between January 2008 and December 2010 were analysed. The long-term survival and response rate were evaluated. Univariate and multivariate analyses were performed to identify the significant predictors of survival. Results: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Post-SBRT, improvement in abdominal pain and discomfort was experienced in 92% and 87% of patients respectively. Similarly, Choi et al 18 demonstrated that after palliative RT, pain improved in about 90% of HCC's patients.…”
Section: Discussionmentioning
confidence: 89%
“…Post-SBRT, improvement in abdominal pain and discomfort was experienced in 92% and 87% of patients respectively. Similarly, Choi et al 18 demonstrated that after palliative RT, pain improved in about 90% of HCC's patients.…”
Section: Discussionmentioning
confidence: 89%
“…5 Choi et al has reported mOS of 13.3 months in pts with Hep B-related BCLC-C group of patients. 6 Evolving evidence has also suggested that concurrent use of immunotherapy with SBRT (SBRT-IO) has resulted in more powerful immune activation effects. In a study by Chiang et al, the overall response rate (ORR) was 87.5% (CR: 50%, PR: 37.5%) in the SBRT-IO arm as compared with 17% (CR: 2.4%, PR: 14.3%) in the TACE alone group.…”
mentioning
confidence: 99%